Answer:
a)
,
, b)
,
, c)
,
.
Step-by-step explanation:
The equation of the circle is:
![x^{2} + (y-1)^{2} = 16](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B%20%28y-1%29%5E%7B2%7D%20%3D%2016)
After some algebraic and trigonometric handling:
![\frac{x^{2}}{16} + \frac{(y-1)^{2}}{16} = 1](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%7D%7B16%7D%20%2B%20%5Cfrac%7B%28y-1%29%5E%7B2%7D%7D%7B16%7D%20%3D%201)
![\frac{x^{2}}{16} + \frac{(y-1)^{2}}{16} = \cos^{2} t + \sin^{2} t](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%7D%7B16%7D%20%2B%20%5Cfrac%7B%28y-1%29%5E%7B2%7D%7D%7B16%7D%20%3D%20%5Ccos%5E%7B2%7D%20t%20%2B%20%5Csin%5E%7B2%7D%20t)
Where:
![\frac{x}{4} = \cos t](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B4%7D%20%3D%20%5Ccos%20t)
![\frac{y-1}{4} = \sin t](https://tex.z-dn.net/?f=%5Cfrac%7By-1%7D%7B4%7D%20%3D%20%5Csin%20t)
Finally,
![x = 4\cdot \cos t](https://tex.z-dn.net/?f=x%20%3D%204%5Ccdot%20%5Ccos%20t)
![y = 1 + 4\cdot \sin t](https://tex.z-dn.net/?f=y%20%3D%201%20%2B%204%5Ccdot%20%5Csin%20t)
a)
,
.
b)
,
.
c)
, ![y = 1 + 4\cdot \sin t''](https://tex.z-dn.net/?f=y%20%3D%201%20%2B%204%5Ccdot%20%5Csin%20t%27%27)
Where:
![4\cdot \cos t' = 0](https://tex.z-dn.net/?f=4%5Ccdot%20%5Ccos%20t%27%20%3D%200)
![1 + 4\cdot \sin t' = 5](https://tex.z-dn.net/?f=1%20%2B%204%5Ccdot%20%5Csin%20t%27%20%3D%205)
The solution is ![t' = \frac{\pi}{2}](https://tex.z-dn.net/?f=t%27%20%3D%20%5Cfrac%7B%5Cpi%7D%7B2%7D)
The parametric equations are:
![x = 4\cdot \cos \left(t+\frac{\pi}{2} \right)](https://tex.z-dn.net/?f=x%20%3D%204%5Ccdot%20%5Ccos%20%5Cleft%28t%2B%5Cfrac%7B%5Cpi%7D%7B2%7D%20%20%5Cright%29)
![y = 1 + 4\cdot \sin \left(t + \frac{\pi}{2} \right)](https://tex.z-dn.net/?f=y%20%3D%201%20%2B%204%5Ccdot%20%5Csin%20%5Cleft%28t%20%2B%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%5Cright%29)
Answer:
y= -2x -8
Step-by-step explanation:
I will be writing the equation of the perpendicular bisector in the slope-intercept form which is y=mx +c, where m is the gradient and c is the y-intercept.
A perpendicular bisector is a line that cuts through the other line perpendicularly (at 90°) and into 2 equal parts (and thus passes through the midpoint of the line).
Let's find the gradient of the given line.
![\boxed{gradient = \frac{y1 -y 2}{x1 - x2} }](https://tex.z-dn.net/?f=%5Cboxed%7Bgradient%20%3D%20%20%5Cfrac%7By1%20-y%202%7D%7Bx1%20-%20x2%7D%20%7D)
Gradient of given line
![= \frac{1 - ( - 5)}{3 - ( - 9)}](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B1%20-%20%28%20-%205%29%7D%7B3%20-%20%28%20-%209%29%7D%20)
![= \frac{1 + 5}{3 + 9}](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B1%20%2B%205%7D%7B3%20%2B%209%7D%20)
![= \frac{6}{12}](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B6%7D%7B12%7D%20)
![= \frac{1}{2}](https://tex.z-dn.net/?f=%20%3D%20%20%20%5Cfrac%7B1%7D%7B2%7D%20)
The product of the gradients of 2 perpendicular lines is -1.
(½)(gradient of perpendicular bisector)= -1
Gradient of perpendicular bisector
= -1 ÷(½)
= -1(2)
= -2
Substitute m= -2 into the equation:
y= -2x +c
To find the value of c, we need to substitute a pair of coordinates that the line passes through into the equation. Since the perpendicular bisector passes through the midpoint of the given line, let's find the coordinates of the midpoint.
![\boxed{midpoint = ( \frac{x1 + x2}{2} , \frac{y1 + y2}{2}) }](https://tex.z-dn.net/?f=%5Cboxed%7Bmidpoint%20%3D%20%28%20%5Cfrac%7Bx1%20%2B%20x2%7D%7B2%7D%20%2C%20%5Cfrac%7By1%20%2B%20y2%7D%7B2%7D%29%20%20%7D)
Midpoint of given line
![= ( \frac{3 - 9}{2} , \frac{1 - 5}{2} )](https://tex.z-dn.net/?f=%20%3D%20%28%20%5Cfrac%7B3%20%20-%20%209%7D%7B2%7D%20%2C%20%5Cfrac%7B1%20-%205%7D%7B2%7D%20%29)
![= ( \frac{ - 6}{2} , \frac{ - 4}{2} )](https://tex.z-dn.net/?f=%20%3D%20%28%20%5Cfrac%7B%20-%206%7D%7B2%7D%20%20%2C%20%5Cfrac%7B%20-%204%7D%7B2%7D%20%29)
![= ( - 3 , - 2)](https://tex.z-dn.net/?f=%20%3D%20%28%20-%203%20%2C%20-%202%29)
Substituting (-3, -2) into the equation:
-2= -2(-3) +c
-2= 6 +c
c= -2 -6 <em>(</em><em>-</em><em>6</em><em> </em><em>on both</em><em> </em><em>sides</em><em>)</em>
c= -8
Thus, the equation of the perpendicular bisector is y= -2x -8.
<span>$ 3,450.00
</span>Equation:
A = P(1 + rt)
Answer:
51
Step-by-step explanation:
Hope this helps. . .